2015
DOI: 10.1007/s11011-015-9725-6
|View full text |Cite|
|
Sign up to set email alerts
|

Ferulic acid chronic treatment exerts antidepressant-like effect: role of antioxidant defense system

Abstract: Oxidative stress has been claimed a place in pathophysiology of depression; however, the details of the neurobiology of this condition remains incompletely understood. Recently, treatments employing antioxidants have been thoroughly researched. Ferulic acid (FA) is a phenolic compound with antioxidant and antidepressant-like effects. Herein, we investigated the involvement of the antioxidant activity of chronic oral FA treatment in its antidepressant-like effect using the tail suspension test (TST) and the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 52 publications
0
31
1
Order By: Relevance
“…improvement of TST and FST scores without affecting locomotor activity; amelioration of SOD, CAT in the blood and cerebral cortex, amelioration of GPx in the cerebral cortex; decrease of thiobarbituric acid-reactive substances’ levels in the blood, hippocampus and cerebral cortex in mice [10];…”
Section: Figurementioning
confidence: 99%
“…improvement of TST and FST scores without affecting locomotor activity; amelioration of SOD, CAT in the blood and cerebral cortex, amelioration of GPx in the cerebral cortex; decrease of thiobarbituric acid-reactive substances’ levels in the blood, hippocampus and cerebral cortex in mice [10];…”
Section: Figurementioning
confidence: 99%
“…In fact, Lenzi et al. has demonstrated that FA exerts antidepressant‐like effects through modulation of the antioxidant defense system . Another recent study has reported that the antidepressant‐like effects of FA observed in epileptic animal model were mediated by its anti‐inflammatory properties .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have stated the protective effect of rice bran phytonutrients, such as beta-carotene, vitamin E and N-acetylcysteine against LPS induced oxidative stress in rats brain (Kheir-Eldin et al, 2001). In vivo studies confirmed that ferulic acid treatment ameliorates the behavioral abnormalities and decreases the antioxidative enzymes activity, and endogenous glutathione level (Lenzi et al, 2015). Studies have shown that treatment with gamma-oryzanol rich rice bran extract to the stressed rat normalizes the expression of oxidative stress-related genes and antioxidant levels (Ismail, Al-Naqeeb, bin Mamat, & Ahmad, 2010).…”
Section: Discussionmentioning
confidence: 95%